Ionic strength induced electrodeposition: a universal approach for nanomaterial deposition at selective areas - Liu, Chang; Long, Yi; Magdassi, Shlomo; Mandler, Daniel (NANOSCALE, 2017)
An appealing alternative approach to the conventional electro-chemical deposition is presented, which can be universally utilized to form nanomaterial coatings from their aqueous dispersions without involving their oxidation-reduction. It is based on altering the ionic strength by electrical potential in the vicinity of the electrode surface, which causes the nanomaterials to deposit. The concept has been demonstrated for four different systems.